Metastatic Malignant Peripheral Nerve Sheath Tumor to the Thyroid - Beatriz, Sanchez; Jose, Dutra; Ritu, Nayar; Xiaoqi, Lin (Journal of Thyroid Cancer, 2015)
It is extremely rare that sarcomas metastasize to the thyroid. We report a case of a 49 year old male with malignant peripheral nerve sheath tumor (MPNST) metastatic to the thyroid that was diagnosed by ultrasound guided fine needle aspiration (FNA). The FNA cytology showed numerous loosely cohesive pleomorphic small spindle cells, some of which were arranged in short fascicles or haphazard pattern. The nuclei were oval or spindle in shape, with hyperchromatic granular chromatin and inconspicuous nucleoli, and smooth nuclear membrane contours. The cytoplasm was scant to moderate in amount, and delicate. Some cells had long thin cytoplasmic projections. Based on the cytomorphology, a diagnosis of “consistent with metastatic MPNST from small intestine” was rendered and follow-up thyroidectomy confirmed the cytologic diagnosis. Therefore, FNA biopsy is a useful, easy to perform, cost effective, safe procedure that can diagnose secondary tumors of the thyroid, and help avoid unnecessary thyroidectomy in patients with a poor prognosis.
Keywords: Thyroid; MPNST; metastasis; fine needle aspiration